Oman in Transition: A Reading of the Post colonial Depiction of Oman in JokhaAlharthi’s Celestial Bodies - Mathew , Nikhitha Mary (International Journal of Psychosocial Rehabilitation, 2020)
Celestial Bodies is JokhaAlharthi’s second novel and the first novel from Arabia to receive the Man Booker Prize (2019). Dealing with the themes of love, madness, slavery and heartbreaks, the novel is also noted for its poetic mode of narration. Through multiple narrators, Alharthi makes sure to explain the gradual evolution the lands and minds have undergone in Oman. The long list of narrators range from Abdullah, his daughter London, slave Zarifa, wife Maaya to name a few. Alharthi also makes it a point to make each of these characters contribute in explaining the evolution that their land has undergone. From the days of slavery to the time when naming a girl London is considered normal, beliefs had a gradual and evident evolution. This paper aims at analysing the post-colonial changes that Alharthi explains and also their impact on Omanian lives. From Zarifa, who believed herself to be her master’s property, to her son who asserts his right over freedom, the novel depicts slavery as one of the most evident postcolonial change that the land witnessed. Apart from slavery, education, emigration and gender equality are also parameters within which the postcolonial changes will be analysed. The paper would shine light upon how this novel depicts postcolonial changes within Oman through its multiple narrators.